Introducing the keyconcept approach to the analysis of language: the case of regulation in COVID-19 diaries - Robinson, Justyna A.; Sandow, Rhys J.; Piazza, Roberta (Frontiers in Artificial Intelligence, 2023)
Using the Mass Observation corpus of 12 th of May Diaries, we investigate concepts that are characteristic of the first coronavirus lockdown in the UK. More specifically, we extract and analyse concepts which are distinctive of the discourses produced in May 2020 in relation to concepts used in the ten previous years, 2010-2019. In the current paper we focus on the concept of REGULATION, which we identify through a novel approach to querying semantic content in large datasets. Typically, linguists look at keywords to understand differences between two datasets (e.g. Love & Baker 2015; Hansen 2016). We demonstrate that taking the perspective of a keyconcept rather than the keyword in linguistic analysis is a beneficial way of identifying trends in broader patterns of thoughts and behaviours which reflect lived-experiences that are particularly prominent of a given dataset, which, in this current paper, is the Covid-19 era dataset. In order to contextualise the keyconcept analysis, we investigate the discourses surrounding the concept of REGULATION. We find that diarists communicate collective experience of limited individual agency, surrounded by feelings of fear and gratitude. Diarists' reporting on events is often fragmented, focussed on new information, and firmly placed in a temporal frame.